2021
DOI: 10.1080/19490976.2021.1957408
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of the intestinal virome and altered viral-bacterial interactions caused by a conditional deletion of the vitamin D receptor

Abstract: Vitamin D receptor (VDR) deficiency is associated with cancer, infection, and chronic inflammation. Prior research has demonstrated VDR regulation of bacteria; however, little is known regarding VDR and viruses. We hypothesize that VDR deficiency impacts on the intestinal virome and viral-bacterial interactions. We specifically deleted VDR from intestinal epithelial cells (VDR ΔIEC ), Paneth cells (VDR ΔPC ), and myeloid cells (VDR ΔLyz ) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 96 publications
1
30
0
Order By: Relevance
“…Our studies support the critical role of VDR in maintaining intestinal and microbial homeostasis [9][10][11] . We established the first conditional deletion of intestinal epithelial VDR mouse model (VDR ΔIEC ) and demonstrated that intestinal bacterial abundance and function are significantly altered in VDR ΔIEC mice 7,12 .…”
Section: Introductionsupporting
confidence: 82%
“…Our studies support the critical role of VDR in maintaining intestinal and microbial homeostasis [9][10][11] . We established the first conditional deletion of intestinal epithelial VDR mouse model (VDR ΔIEC ) and demonstrated that intestinal bacterial abundance and function are significantly altered in VDR ΔIEC mice 7,12 .…”
Section: Introductionsupporting
confidence: 82%
“…By constructing knockout mice with specific deletion of VDR in IECs (VDR∆IEC), Paneth cells (VDR∆PC) and myeloid cells (VDR∆Lyz), Jilei Zhang et al analyzed the bacterial and viral composition and metabolites of each group of mice and found that tissue-specific deletion of VDR altered the viral population and functionally changed the viral receptor, which resulted in ecological dysregulation, metabolic dysfunction, and infection risk. Expression of TLR3/7, NOD1/2, and NLR6 was upregulated in knockout mice, and C-type lectin receptor 4L (CLR4L) was significantly upregulated (Figure 2) [93]. Overall, the significant alterations in pattern recognition receptors (PRRs) of conditional VDR knockout mice indicate an impact of VDR on intestinal homeostasis and PRRS expression.…”
Section: Intestinal Immune Cells and Their Secreted Substancesmentioning
confidence: 90%
“…Lack of VDR in Paneth cells can lead to viral dysregulation, which may further lead to impaired epithelial barrier function. VDR activation has a regulatory role in enterovirus-host interactions [91][92][93]. This suggests that VDR could be a potential target for study in bacterial-viral-host interactions.…”
Section: Intestinal Immune Cells and Their Secreted Substancesmentioning
confidence: 99%
“… 136 Deletion of VDR in mouse intestinal epithelial cells results in fecal dysbiosis, metabolic dysfunction, and increased risk of infection. 137 Sun et al also demonstrated that intestinal epithelial VDR knockout mice had abnormal Paneth cell function, impaired autophagy, and dysbiosis, along with downregulation of ATG16L1, a regulator of autophagy, and are susceptible to colitis. 138 In addition, intestinal epithelial VDR deficiency increases epithelial cell apoptosis and impairs cell autophagy by decreasing ATG16L1 and Beclin-1 expression.…”
Section: Vitamin D and Ibd Pathogenesismentioning
confidence: 99%